Influence of resistance training volume and periodization on physiological and performance adaptations in collegiate women tennis players - Kraemer, W. J.; Ratamess, N.; Fry, A. C.; Triplett-McBride, T.; Koziris, L. P.; Bauer, J. A.; Lynch, J. M.; Fleck, S. J. (The American Journal of Sports Medicine, 2000)
Few data exist on the long-term adaptations to heavy resistance training in women. The purpose of this investigation was to examine the effect of volume of resistance exercise on the development of physical performance abilities in competitive, collegiate women tennis players. Twenty-four tennis players were matched for tennis ability and randomly placed into one of three groups: a no resistance exercise control group, a periodized multiple-set resistance training group, or a single-set circuit resistance training group. No significant changes in body mass were observed in any of the groups throughout the entire training period. However, significant increases in fat-free mass and decreases in percent body fat were observed in the periodized training group after 4, 6, and 9 months of training. A significant increase in power output was observed after 9 months of training in the periodized training group only. One-repetition maximum strength for the bench press, free-weight shoulder press, and leg press increased significantly after 4, 6, and 9 months of training in the periodized training group, whereas the single-set circuit group increased only after 4 months of training. Significant increases in serve velocity were observed after 4 and 9 months of training in the periodized training group, whereas no significant changes were observed in the single-set circuit group. These data demonstrate that sport-specific resistance training using a periodized multiple-set training method is superior to low-volume single-set resistance exercise protocols in the development of physical abilities in competitive, collegiate women tennis players.